PENGARUH PENILAIAN PRESTASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI (Studi Pada Unit Pelaksana Teknis Pendidikan Kecamatan Sumbersari Kabupaten Jember) - Ratna Dwi Arini (Jurnal Ilmiah Mahasiswa FEB, 2014)
Purpose  of this  research was to observe  the influence  of performance appraisal which  consists  of  the aspects  are assessed,  appraiser, methods of  appraisal  and feedback  that  influence employee satisfaction  Technical Implementation Unit (UPT) Education Sumbersari District of  Jember,  simultaneously  or partially. To determine the influence of  the dependent variable  (job satisfaction)  of the independent variable  (performance appraisal)  used  multiple linear  regression analysis  with  analysis  method  F test  and t test.  This kind of research is explanatory research, to describes the  connected  and  the influence of  some variables  that have been defined.  The population  at  the same time  the study sample  was  50  employees  Technical Implementation Unit  (UPT)  Education Sumbersari  District of  Jember,  and also  called  the  census  sample.  The results using multiple linear regression analysis showed that there is significant influence between  variables  simultaneously  Aspects  are Assessed  (X1),  Appraiser  (X2), Methods of Apprasal (X3), Feedback (X4) on Employee Job Satisfaction (Y) Unit Technical Implementation (UPT) Education Sumbersari District of Jember, with a significance level of 0.000 and determination coefficient of 0.594 (59.4%). While partially  through  t test known that,  just Variable Appraisers  (X2) showed a value 3.597 with significant 0.001 and also Variables Method of Appraisal (X3) showed a value 1.954 with  significant 0.057 which  indicates partial significant influence on  employee  job satisfaction  (Y). Through  this research,  it is expected that  the Technical Implementation Unit (UPT) Education Sumbersari District of Jember to fix implementation of  performance appraisal,  so as to  improve  employee satisfaction.Keywords:  Job Performance  Appraisal,  Aspects  Are Assessed, Method  Of Appraisal,  Appraiser, Feedback,  Employee  Job  Satisfaction, Technical Implementation Unit (UPT) Education Sumbersari District of Jember.